Dissociating the processing of empty categories in raising and control sentences: a self-paced reading study in Japanese - Yamaguchi, Koki; Ohta, Shinri (Frontiers in Language Sciences, 2023)
Theoretical linguistics has proposed different types of empty categories (ECs), i.e., unpronounced words with syntactic characteristics. ECs are a key to elucidating the computational system of syntax, algorithms of language processing, and their neural implementation. Here we examined the distinction between raising and control sentences in Japanese and whether ECs are psychologically real. We found two striking results by using a self-paced reading and a probe word recognition priming technique. First, we demonstrate that the reading times of raising and control sentences in Japanese were better explained by the linear mixed-effects model considering the differences of ECs, i.e., Copy and PRO. Secondly, we found a significant reactivation effect for raising and control sentences, which have ECs, and reflexive sentences without ECs. These results indicate that ECs are processed similarly to reflexive pronouns (e.g., himself). Based on these results, we conclude that raising and control sentences in Japanese have different ECs, i.e., Copy and PRO, and that ECs have psychological reality. Our results demonstrate that behavioral experiment based on theoretical linguistics, which is the first step for developing linking hypotheses connecting theoretical linguistics and experimental neuroscience, is indeed necessary for testing hypotheses proposed in theoretical linguistics.